Barriers to correct child restraint use: A qualitative study of child restraint users and their needs. (November 2018) - Hall, Alexandra; Ho, Catherine; Keay, Lisa; McCaffery, Kirsten; Hunter, Kate; Charlton, Judith L.; Hayen, Andrew; Bilston, Lynne; Brown, Julie
Highlights: The COM-B Model of Behaviour is applied to understand qualitative barriers to child restraint system (CRS) use. Results show that current CRS product information is poorly understood particularly among CALD users. Lack of information and understanding can lead to errors in the way the restraint is used. Memory, motivation, and attention influence correctness of use, and should be addressed in future educational interventions. Abstract: Motor vehicle crashes are a major cause of death and injury to children worldwide. Although risk of injury to child passengers can be reduced by using a child restraint, most restraints are incorrectly used. This greatly reduces the restraints' protective potential; however there is limited research on drivers of correct child restraint use. The aim of this study was to explore perceived barriers and motivators of correct child restraint use in experienced child restraint users, to inform interventions to promote correct use. Motivations and risk perceptions concerning incorrect child restraint use among high and low socioeconomic populations and culturally and linguistically diverse (CALD) child restraint users in Sydney, Australia were qualitatively examined. Six focus groups (N = 44 participants) were facilitated using a semi-structured discussion guide. Transcriptions were deductively analysed using QSR NVivo11 software and the COM-B model of behaviour. Common perceived barriers to correct restraint use were: (a) difficulty interpreting instructions and labels, particularly among CALD participants; (b) remembering and attending to correct use information; (c) lack of information and behavioural feedback on how to correctly install and use a child restraint; and (d) low confidence in ability to install and use a child restraint correctly. The results indicate current child restraint product information is poorly understood, particularly among those whose first language is not English. Interventions to increase correct child restraint use should address access to correct use information, capability to understand and use these, and the influence of motivation, memory and attention in the process.